Comparison on Rare Gas Geochemical Characteristics and Gas Originations of Kuche and Southwestern Depressions in Tarim Basin, China. (2nd June 2019) - Wang, Xiaobo; Zou, Caineng; Li, Jian; Wei, Guoqi; Chen, Jianfa; Xie, Zengye; Li, Zhisheng; Guo, Jianying; Lin, Shiguo; Pan, Songqi; Hao, Aisheng; Yang, Chunlong; et al.
Abstract : The Kuche Depression is considered as the most important gas resource potential and gas exploring area with great gas resource potential and prospect in the Tarim Basin. Based on geochemical experimental analyses and comprehensive geological studies, the general geochemical characteristics of molecular and isotope compositions of rare gases as well as hydrocarbon gases and nonhydrocarbon gases are comparatively studied in the Kuche and Southwestern Depressions. Then, their genetic types are separately identified and gas originations are comprehensively discussed. The main results are as follows. (1) Gas fields in the Kuche Depression have a higher methane abundance, accompanied with low N2 and CO2 abundances, but the Akemomu gas field in the Southwestern Depression has a relatively lower average methane abundance, accompanied with high average N2 and CO2 abundances. The helium abundance of natural gases in gas fields from the Kuche Depression general has 1 order of magnitude higher than the air value. Comparatively, it has more than 2 orders of magnitude higher than the atmospheric value in the Akemomu gas field from the Southwestern Depression. The neon, argon, krypton, and xenon abundances in both Kuche and Southwestern Depressions are lower than the corresponding air values. (2) Natural gases from gas fields in the Kuche Depression and the Southwestern Depressions are generally typical coal-formed gases. The rare gases in the Kuche Depression have typical crustal genesis, mainly deriving from the radioactive decay of elements in the crust, while in the Akemomu gas field from the Southwestern Depression, the rare gases have main crustal genesis with a proportion of 92.5%, probably accompanied with a little mantled genetic contribution. (3) Natural gases in the Kuche Depression are generally derived from coal measure source rocks of Jurassic and Triassic, which principally originated from Jurassic in strata period and coals in source rock types. The Jurassic source rocks account for 55%-75% and the Triassic source rocks account for 25%-45% approximately, while coals occupy 68% and mudstones occupy 32% separately. Natural gases from the Akemomu gas field in the Southwestern Depression mainly originated from humic mudstones of marine and continental transitional source rocks of Carboniferous to Permian.